2007
DOI: 10.1038/sj.jp.7211792
|View full text |Cite
|
Sign up to set email alerts
|

Unintentional exposure of neonates to conventional radiography in the Neonatal Intensive Care Units

Abstract: Objective: To evaluate the extent of unintentional exposure to X-rays performed during routine diagnostic procedures in the Neonatal Intensive Care Units (NICUs).Study Design: During a 1-month period, 157 consecutive neonates from five level-III NICUs were recruited for this study. The mean birth weight was 1747±911 g (range: 564-4080 g), and gestational age was 31.6±3.6 weeks (range: 24-41 weeks). A total of 500 radiographs were performed including chest (68%), abdomen (17%) and combined chest and abdomen (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 15 publications
3
22
1
Order By: Relevance
“…The median ESD value (0.06 mGy) was higher than those proposed by the National Radiological Protection Board (50 mGy) (Hart et al, 2000) for neonatal chest X-ray examination, but lower than those proposed by the guidelines of the European Commission (80 mGy, European Commission, 1996). Our findings showed that the median ESD values or the number of X-ray procedures performed for each neonate were higher than those reported previously (Sutton et al, 1998;Ono et al, 2003;Donadieu et al, 2006;Bader et al, 2007;Baert et al, 2008;Puch-Kapst et al, 2009). Although low voltage-high tube current time product combination shows good image quality, it could lead to high ESD (Frayre et al, 2012;Porto et al, 2014).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The median ESD value (0.06 mGy) was higher than those proposed by the National Radiological Protection Board (50 mGy) (Hart et al, 2000) for neonatal chest X-ray examination, but lower than those proposed by the guidelines of the European Commission (80 mGy, European Commission, 1996). Our findings showed that the median ESD values or the number of X-ray procedures performed for each neonate were higher than those reported previously (Sutton et al, 1998;Ono et al, 2003;Donadieu et al, 2006;Bader et al, 2007;Baert et al, 2008;Puch-Kapst et al, 2009). Although low voltage-high tube current time product combination shows good image quality, it could lead to high ESD (Frayre et al, 2012;Porto et al, 2014).…”
Section: Discussioncontrasting
confidence: 64%
“…Therefore, mathematical equations have been suggested by several studies to calculate the radiation dose from radiographic examinations, and some reports have shown that the calculated value corresponds to direct measurement value in radiographic examinations (Ishiguchi et al, 2000;Kim et al, 2005). Since we use a mobile X-ray machine that cannot measure DAP, we calculated the ESD using the nondosimeter dosimetry method developed by Mori (Ibaragi Radiological Technologists Association et al, 1996) and compared our findings with those of other studies and reference values (Sutton et al, 1998;Ono et al, 2003;Donadieu et al, 2006;Bader et al, 2007;Baert et al, 2008;Puch-Kapst et al, 2009). The non-dosimeter dosimetry-M equation calculates the ESD according to the rectification method of the photographic equipment.…”
Section: Estimation Of the Patient Radiation Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Correction of this situation does not require investment of resources. By simply raising awareness among the staff with better guidelines regarding exposure to IR, these issues can be resolved (Bader et al, 2007).…”
Section: Reducing Exposure To Ir In Childrenmentioning
confidence: 99%
“…The usage of lead screening may also limit radiation to sensitive tissues such as thyroid, breast and ovaries. In many neonatal ICU centres extra parts of the patient were exposed, for example in 85% of chest x rays the abdomen was also irradiated 11. Protocol-driven process change would limit unnecessary exposure.…”
Section: Discussionmentioning
confidence: 99%